Uncovering the Culture of Osing People in Palatalizing the Consonant Clusters - Galang Fajaryanto; Agus Subiyanto (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2020)
Osing dialect is one of the Javanese dialects used in Banyuwangi, East Java. This dialect has a unique phenomenon called as palatalization that does not exist in other Javanese dialects called as palatalization. Palatalization is an assimilation process that involves the interaction of sounds triggering the palatal articulation. Commonly, palatalization involves two sounds that consist of a single consonant (target) and a single vowel (trigger) as the environment in its appearance. Different from the common palatalization phenomena, the Osing dialect has palatalization in consonant clusters form. In the Osing dialect, there are 21 consonant clusters but only few of the consonant clusters undergo the palatalization. This study aimed to identify the consonant clusters which undergo the palatalization and find the palatalization pattern. The analysis method that we used in this study is descriptive-qualitative method. In the analysis, we also provided a discussion by using generative phonology. The data used in this article were taken from the Osing speaker in Kemiren, Banyuwangi. The result of this analysis showed that the palatalization of consonant clusters happens when the cluster are constructed by two consonants which have voiced features and they are followed by the trigger sounds.